-163

No Study=Fail. Study=No Fail. So, No Study+Study=Fail+No Fail. Then, (No+1)Study=(No+1)Fail. Therefore, Study=Fail. amirite?

Image for post No Study=Fail. Study=No Fail. So, No Study+Study=Fail+No Fail. Then, (No+1)Study=(No+1)Fail. Therefore, Study=Fail. amirite?
19%Yeah You Are81%No Way
Arwens avatar
Share
3 30
The voters have decided that Arwen is wrong! Vote on the post to say if you agree or disagree.

You didn't account for 'no' being equal to -1, which would have meant you couldn't divide through by it.
And to be honest, if I had to give the word 'no' a mathematical value in the context it's used here, it would be -1.

Number3s avatar Number3 No Way +14Reply
@Number3 That wasn't the context it was used here.

It's a math problem, so yes, it was. But I'll take it back if you can name me a context when "no" means -1 rather than 0.

No Study = Fail
Study = No Fail


Study - Study = Fail - Fail
0 = 0 or Study = Study or Fail = Fail, all useless.

So it's nonsense.

Chiffs avatar Chiff No Way +10Reply
@Arwen Of course it's nonsense. It's not meant to be taken seriously.

Yeah but if the math's wrong then what's the point? Here's one that actually works.

Money = Root (Evil)
Time = Money
Girls = Time x Money


Girls = Evil

Chiffs avatar Chiff No Way +9Reply
@Chiff Yeah but if the math's wrong then what's the point? Here's one that actually works. Money = Root (Evil) Time =...

d smilie

The point is that it's amusing, even though it may technically be incorrect. Like the "proof" that 1=2. Or that all horses are the same color... iss interesting, no?

Arwens avatar Arwen Yeah You Are -1Reply
@Chiff proof that 1=2?

Let a and b be equal positive real numbers.

1. a=b
2. a2=ab
3. a2-b2=ab-b2
4. (a-b)(a+b)=b(a-b) <--factored from previous step
5. a+b=b <--canceled a-b
6. b+b=b <--since a=b
7. 2b=b
8. 2=1

Sure it's incorrect, but finding out what's wrong with it is part of the fun. :D

Arwens avatar Arwen Yeah You Are 0Reply
@Arwen Let a and b be equal positive real numbers. 1. a=b 2. a2=ab 3. a2-b2=ab-b2 4. (a-b)(a+b)=b(a-b) <--factored...

Here's an easier one:
Start with 2=1
Subtract 1.5 from both sides: .5=-.5
Square both sides: (.5)2=(-.5)2
Result: .25=.25
Works with any two numbers, just take the average of the two numbrrs and subtract from both sides.

@Arwen huh. I haven't seen that one before. I like it.

Thanks, my 7th grade math teacher showed us that when trying to explain why you shouldn't set things equal to each other in a proof.

@theoneandonlyspaz Here's an easier one: Start with 2=1 Subtract 1.5 from both sides: .5=-.5 Square both sides:...

Nice, but frankly I was more intrigued by the fact that -.5 looks like Patrick Moore.

Chiffs avatar Chiff No Way +1Reply
@theoneandonlyspaz Here's an easier one: Start with 2=1 Subtract 1.5 from both sides: .5=-.5 Square both sides:...

strictly speaking it should be:
(.5)2=(-.5)2
±0.25 = ±0.25
You might as well say 1+1= 3 so 1≠1

@Chiff Umm all you've done is proven that A and B are 0?

No, that would contradict the original assumption that a and b are positive. The problem's somewhere else.

Arwens avatar Arwen Yeah You Are 0Reply
@Chiff This is killing me man XD

If a=b then you can't cancel a-b because a-b=0, which you can't divide by.

@Chiff This is killing me man XD

I know, right? Therein lies the fun. :P

Arwens avatar Arwen Yeah You Are -1Reply

Where no+1 come from?

@PeanutButterRatio Where no+1 come from?

You'd understand if you were good at maths.

@PeanutButterRatio Where no+1 come from?

He took study common from no study and study.

@PeanutButterRatio Where no+1 come from?

It's just rewriting it to equal the same thing. Either the fail or the study would be distributed to the no and the 1, so it comes to be no study+ study. The same would go for fail. Get it?

Before someone calls foul, I know this is not original. I just can't remember where I first saw it so I didn't know how to give credit.

Arwens avatar Arwen Yeah You Are +1Reply

No Study + Study = Fail + No Fail
No Study - No Fail = Fail - Study
No (Study - Fail) = -1(Study - Fail)
No = -1
No + 1 = 0
And in the last two steps, dividing by (No + 1) is dividing by 0, which you can't do.

Fail

Anonymous 0Reply
Please   login   or signup   to leave a comment.